Association of pulsatile stress in childhood with subclinical renal damage in adults: A 30‐year prospective cohort study. Issue 10 (8th September 2021) - Liao, Yueyuan; Chu, Chao; Wang, Yang; Zheng, Wenling; Ma, Qiong; Hu, Jiawen; Yan, Yu; Yang, Jun; Yang, Ruihai; Wang, Keke; Yuan, Yue; Chen, Chen; et al.
Abstract: The pulsatile stress in the microcirculation may contribute to development or progression of chronic kidney disease. However, there is no prospective data confirming whether pulsatile stress in early life affect renal function in middle age. The authors performed a longitudinal analysis of 1738 participants aged 6–15 years at baseline, an ongoing Adolescent Prospective Cohort with a follow‐up of 30 years. The authors evaluated the association between pulsatile stress in childhood and adult subclinical renal damage (SRD), adjusting for related covariates. Pulsatile stress was calculated as resting heart rate × pulse pressure. Renal function was assessed with estimated glomerular filtration rate (eGFR) and urine albumin‐to‐creatinine ratio (uACR). The results showed that pulsatile stress in childhood was associated with adult SRD (Relative Risk, 1.43; p  = .032), and the predictive value of combined pulse pressure and heart rate for SRD was higher than either of them alone. The high pulsatile stress in childhood increased the risk of adult SRD in males (RR, 1.92; p  = .003), but this association was not found in females (RR, 0.91; p  = .729). Further, the participants were categorized into four groups on the basis of pulsatile stress status in childhood and adulthood. Male patients with high pulsatile stress during childhood but normal pulsatile stress as adults still had an increased risk of SRD (RR, 2.04; 95% CI, 1.18–3.54), while female patients did not (RR, 0.96; 95% CI, 0.46–1.99). The study demonstrated that high pulsatile stress in childhood significantly increased the risk of adult SRD, especially in males. Adequate control of pulse pressure and heart rate from childhood, in the long‐term, is very important for preventing kidney damage.